Mesin Multifungsi bagi petani Jagung Di Desa Buntu Bedimbar - Thamrin, Husni; Siagian, Tony; Hasibuan, Edi Sarman; Eswanto, Eswanto (UKInstitute, 2024)
Buntu Bedimbar Village is a village located on Jalan Batang Kuis Pasar VIII, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. The location of this village is a rural area where there are still many fields or rice fields that are used for farming to meet living needs. The urgency of this community service is related to partner problems, namely the absence of tools or technology that can assist in the process of peeling, shelling and chopping corn cobs, all work activities are carried out manually which in the end prolongs the work process time and has an impact on obtaining final results that are not optimal. The solution is to create a mechanical system of tools/machines for peeling, shelling and chopping corn cobs, to speed up the work process of corn farmers. The aim of this community service is to help solve problems faced by partners, namely by applying appropriate technology in the form of a multifunctional machine combining shellers, shellers and corn cob choppers using mechanical power that has been assembled in the mechanization of one work system. The implementation method is by coming directly to the location. partners, discussions look for partners' problems and then provide a solution, namely by making a multifunctional tool with a combination of mechanical system peeler, sheller and corn chopper. This tool works once to produce 3 outputs in the form of (corn peeler, corn sheller and corn cob chopper). The results of community service activities that have been carried out to date show that the community can accept this activity well, the tools provided can function and can help ease the work of corn farmers, especially during the harvest season.